"[L]abels of Themselves Condition Our Perceptions": The DSM and the Diagnostic Sign of Schizophrenia. Issue 1 (January 2015) - Flexer, Michael J.
Abstract The American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM) has been partitioning mental illnesses into discrete disease entities for over 60 years. The diagnostic class of schizophrenia has undergone several different labels and some profound changes to its criteria over all these iterations. In trying to develop the least‐imperfect pragmatic description, the DSM has had to make several assumptions about the disease, and over the various iterations several critics – from within and without psychiatry – have increasingly felt that the APA have accepted their own assumptions as truth, creating a self‐justifying and self‐perpetuating ideology of schizophrenia. The latest edition, DSM‐5, has incorporated some of this criticism, but it is unclear whether the dominant ideology of the diagnostic labels will be over‐turned or will simply incorporate this challenge to its authority into its own "continuity myth" of ever‐improving diagnostic criteria.